2011
DOI: 10.2507/ijsimm10(2)2.173
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the 3D machining geometric defects accounting for workpiece vibratory behaviour

Abstract: In this paper, we present a three-dimensional manufacturing tolerancement model. Several researchers have interested to modelling the machining geometric defects. The most researchers are limited to kinematic and static study. Only some works are evoked the dynamic effects, especially the influence of the chatter phenomenon on the roughness of the machined surface. In this context, the paper presents a contribution for modelling and quantification of the machining geometric defects where the machining dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…AE signals as a result of their research have demonstrated that an important indicator for quality of laser cut. The number of studies related to 3D machining [22] and tool life [23] were also studied by the researchers.…”
Section: Introductionmentioning
confidence: 99%
“…AE signals as a result of their research have demonstrated that an important indicator for quality of laser cut. The number of studies related to 3D machining [22] and tool life [23] were also studied by the researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Vishnupriyan et al [24] determined optimal fixture layout to minimize the machining error considering locator geometric error and workpiece elastic deformation. Chaari et al [25] presented a modelling methodology for geometrical machining defect. The kinematical deviation due to part locating and relocating was modelled by homogeneous transformation.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of tool geometries on performance measures of flank wear, surface roughness and cutting forces generated were evaluated. Chaari et al [15] presented a contribution for modelling and quantification of the machining geometric defects, considering machining dynamic effects. A method was developed based on Homogeneous Transformation Method.…”
Section: Introductionmentioning
confidence: 99%